An empirical comparative study of the circular economy from a consumer perspectıve: Malaysia vs Turkey - Jan, Muhammad Tahir (2020)
Irresponsible production and consumption of products are the main reason for environmental decimation. To mitigate this alarming burden on the environment, a new approach has been proposed, called “The Circular Economy”. The main objective of this system is to introduce new systems of production, consumption, and disposal, for growing global prosperity. This philosophy is also aligned with the United Nations goals of sustainability, commonly known as SDGs, particularly, the goal of responsible production and consumption (SDG No. 12). Circular economy from a marketing perspective has been hardly explored and/or investigated. This research, therefore, attempts to extract and empirically investigate those critical factors related to the circular economy that have an impact on consumer behaviour in general, and consumer purchase intention in particular. For this purpose, the theory of planned behaviour is adapted with the addition of two more factors related to the circular economy, which are convenience/ availability, and environmental impact, as extracted from the literature to examine their effect on consumer purchase intention. Data were collected from two countries Malaysia and Turkey, in order to undertake the comparative analysis. A total of 377 consumers of circular products from Malaysia, and 351 consumers from Turkey, were used for data analysis. Complex statistical techniques like exploratory factor analysis and structural equation modelling with confirmatory factor analysis and hypotheses testing were used to analyse the data. Structural Model Comparison (Structural Invariance) was used to compare the model of Malaysia with that of the model of Turkey. Interesting findings emerged, which will certainly contribute to helping policy-makers devise strategies that are not only sustainable and aligned with the philosophy of the circular economy but will also ensure positive consumer behaviour.